Hydroxychloroquine, cold urticaria, and the ice bucket challenge: A case report - Ribal Merhi; Nakhle Ayoub; Carla Hajj; Marc Mrad (Wolters Kluwer Medknow Publications, 2017)
Background: Cold urticaria is often resistant to first line treatment with second-generation H1-antihistamines. Case summary: We report a case of a fifty year-old woman with a history of cold urticaria showing no response to classic treatments, treated successfully with hydroxychloroquine initially prescribed to treat her frontal fibrosing alopecia. Conclusion: Hydroxychloroquine may be a successful treatment option for recalcitrant cold urticaria.